THE IMPLEMENTATION OF HOMOPHONE GAMES TO IMPROVE STUDENTS’ LEXICAL MASTERY AT SEVENTH-GRADE STUDENTS OF SMP NEGERI 1 PETERONGAN JOMBANG - Maujudatul Mufidah, Zahratul; Mustofa, Ihyak; Daniati, Apriliah (Critical Review of English-Arabic World Journal, 2023)
The objectives of the study is to determine the implementation of homophone games to improve students’ lexical mastery at seventh-grade students of Sekolah Menengah Pertama Negeri 1 Peterongan Jombang. The research applied a classroom action research as research method. It was conducted in Sekolah Menengah Pertama Negeri 1 Peterongan Jombang. The data were gathered by test, observations and documentation. The results of this research that implementing Homophone Games to improve students’ lexical mastery in the seventh grade of SMP Negeri 1 Peterongan can help students improve their lexical mastery.